Pushmepullyou. (Economist, 1996)
Evaluates the difference between the World Wide Web and the rest of the Internet, using the analogy of the difference between motion pictures and television; Excess of choice on the Web, and the difficulties this poses for the viewer; Reasons why the Web attracts more viewers more than electronic mail alone; Information on the Castanet technology from the company Marimba Inc.; Concerns about a return to lowest-common-denominator programming, as in television.